2018
DOI: 10.1596/1813-9450-8478
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Costs of Financial Intermediation around the World

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
(41 reference statements)
4
16
0
Order By: Relevance
“…This finding was also reported by Rojas-Suarez (2001) in her analysis of financial indicators in emerging markets, where she highlights that neither profitability ratio nor the cost ratio are useful indicators for discerning between strong and weak banks in developing countries. These results show that the banks across this region have a specific idiosyncrasy regarding costs, since financial intermediation expenses in the region are particularly high (Calice and Zhou 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…This finding was also reported by Rojas-Suarez (2001) in her analysis of financial indicators in emerging markets, where she highlights that neither profitability ratio nor the cost ratio are useful indicators for discerning between strong and weak banks in developing countries. These results show that the banks across this region have a specific idiosyncrasy regarding costs, since financial intermediation expenses in the region are particularly high (Calice and Zhou 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…The study conducted by Stiglitz and Weiss (1981) found that credit rationing is prioritized for a higher cost of financial intermediation results in a lower level of credit grant to borrowers. The cost of financial intermediation is higher for lower-income countries (Calice & Zhou, 2018), and hence the lower intermediation spread is driven as a causal factor for financial development. The study found similar results concerning the cost of financial intermediation, which is negatively associated with bank risk and cost-efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…1. Operational costs: Staff and administrative costs are transferred to borrowers and depositors and typically form the largest component in lending rates and spreads (De la Torre Poghosyan, 2012;Calice and Zhou, 2018). Operational costs are typically lower in larger banking systems, which initially have more capacity to generate economies of scale, and in a favorable business environment which, inter alia, allows for more accurate borrower screening, better contract enforcement, and higher collateral recovery.…”
Section: B Drivers Of Bank Interest Rates and Spreadsmentioning
confidence: 99%
“…3. Quasi-taxes: Monetary and macro-prudential policy instruments such as (not fully) remunerated reserves and counter-cyclical capital buffers represent a regulatory cost for banks (Brock and Rojas, 2000;Saunders and Schumacher, 2000;Gelos, 2006;De la Torre et al, 2006;Calice and Zhou, 2018). Moreover, directed lending and interest subsidy programs, interest rate restrictions, and other "financial repression"-type tools affect rates and spreads.…”
Section: B Drivers Of Bank Interest Rates and Spreadsmentioning
confidence: 99%
See 1 more Smart Citation